2018
DOI: 10.1167/iovs.18-23951
|View full text |Cite
|
Sign up to set email alerts
|

CD34 Orbital Fibroblasts From Patients With Thyroid-Associated Ophthalmopathy Modulate TNF-α Expression in CD34+ Fibroblasts and Fibrocytes

Abstract: PurposeOrbital fibroblasts from patients with Graves' disease (GD-OF) express many different cytokines when treated with bovine thyrotropin (bTSH). The present study aimed to determine why TNF-α cannot be induced by bTSH in GD-OF.MethodsFibrocytes and GD-OFs were cultivated from donors who were patients in a busy academic medical center practice. Real-time PCR, Western blot analysis, reporter gene assays, cell transfections, mRNA stability assays, ELISA, and flow cytometry were performed.ResultsWe found that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…Apart from orbital fibroblasts, fibrocytes, which are CD34 + bone marrow-derived progenitor cells, migrate from the circulation into sites of inflammation and injury ( Figure 2). They have been identified in the orbit, particularly those of patients with Graves' orbitopathy, 92,93 and reported to express two of the major thyroid autoantigens, the TSHR and thyroglobulin 94 Graves' orbitopathy and non-Graves' orbitopathy orbital fibroblasts 97 . Mast cells also produce prostaglandins which are able to enhance adipogenesis 98 .…”
Section: [H2] Rituximabmentioning
confidence: 99%
“…Apart from orbital fibroblasts, fibrocytes, which are CD34 + bone marrow-derived progenitor cells, migrate from the circulation into sites of inflammation and injury ( Figure 2). They have been identified in the orbit, particularly those of patients with Graves' orbitopathy, 92,93 and reported to express two of the major thyroid autoantigens, the TSHR and thyroglobulin 94 Graves' orbitopathy and non-Graves' orbitopathy orbital fibroblasts 97 . Mast cells also produce prostaglandins which are able to enhance adipogenesis 98 .…”
Section: [H2] Rituximabmentioning
confidence: 99%
“…This receptor was subsequently found to be functional and could mediate effects of both TSH and thyroid-stimulating autoantibodies (7,14). Activation of several genes, including those encoding cytokines implicated in the pathogenesis of TAO, has been reported (19,(33)(34)(35). Fibrocytes are trafficked to sites of tissue injury through several chemokine networks, most notably the CXCL-12/CXCR4 pathway (36) which is under the control of TSHR signaling.…”
Section: Current Understanding Of Tao Pathogenesismentioning
confidence: 99%
“…Some studies have pointed out that this regulatory effect may be controlled by Slit2 and AIRE. [ 72 73 74 75 ] Our study found that fibrocytes can recruit Th17 cells through the MIP-3/CCR-6 pathway. [ 76 ] In addition, TSH and CD40L can induce the secretion of IL-12 of fibrocytes,[ 77 ] which might be involved in the induction of Th1 cell immunity or transformation of Th17 cell to Th1 phenotype.…”
Section: Fibrocytesmentioning
confidence: 83%